2010
DOI: 10.1007/s10646-010-0504-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the suitability of application of golden jackal (Canis aureus) hair as a noninvasive technique for determination of body burden mercury

Abstract: An evaluation of suitability of applying hair as a noninvasive indicator for determination of the body burden mercury in mammals was carried out by determining the concentration of mercury in hair and liver tissue of the golden jackal, Canis aureus . Nineteen jackals killed on the roads along the Caspian Sea in the central region of Mazandaran Province, Iran were collected. The mercury measurements were carried out by AMA254 LECO and the standard method ASTM-D6722. SPSS and Excel were used for analytical stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…It is worth to note, that Hac et al (1996) found positive correlation between Hg content of the hair, kidneys, blood, and urine of A-I means in columns marked with the same upper case differ significantly at P ≤ 0.01 a-g means in columns marked with the same lower case differ significantly at P ≤ 0.05 rats intoxicated with mercury chloride. Statistically significant correlation (r = 0.321) was noted between Hg concentration in the hair and liver content of golden jackal (Canis aureus) (Malvandi et al 2010). Thus, the noninvasively collected hair samples may be useful in the assessment of heavy metals bioaccumulation in animal organs.…”
Section: Effect Of Speciesmentioning
confidence: 99%
“…It is worth to note, that Hac et al (1996) found positive correlation between Hg content of the hair, kidneys, blood, and urine of A-I means in columns marked with the same upper case differ significantly at P ≤ 0.01 a-g means in columns marked with the same lower case differ significantly at P ≤ 0.05 rats intoxicated with mercury chloride. Statistically significant correlation (r = 0.321) was noted between Hg concentration in the hair and liver content of golden jackal (Canis aureus) (Malvandi et al 2010). Thus, the noninvasively collected hair samples may be useful in the assessment of heavy metals bioaccumulation in animal organs.…”
Section: Effect Of Speciesmentioning
confidence: 99%
“…Previous general studies, targeting all mammals of Iran in which golden jackal distribution is addressed, are often at a course scale (e.g., Etemad, 1985;Yusefi, Faizolahi, et al, 2019;Ziaie, 2008), and very few specific studies focusing Iranian golden jackals have been published in international peer-reviewed journals. To our knowledge, there are only three of these works, related to (a) methodological procedures for determination of body burden mercury using hair from jackals (Malvandi et al, 2010)…”
Section: Distribution Pattern and Habitat Selectionmentioning
confidence: 99%
“…In fur‐bearing animals, it frequently has been observed that Hg levels in the hair are correlated to Hg concentrations in other tissues . Some studies have suggested that fur could be used as a noninvasive technique to determine Hg and/or MeHg concentrations in other tissues and organs , similar to what has been implemented in humans, whereby hair is used as a biological indicator of MeHg exposure .…”
Section: Introductionmentioning
confidence: 99%